Critical possibilities for painting after neo-expressionism - Burgener, Andrea (My University, 2017)
Painting as a practice has been probk-matlsed in postmodern discourse in many ways. Neo-expressionism painting has been seen by certain Inf'luental critics as standing for a particularly regressive form of painting. These critics argue- that Neo-expressionism painting perpetuates dominant (mascullnlst) values. This dissertation examines how these critiques of Neo-expressionisrn might open up a space for a re-arttculatlon of painting. More specifically, it proposes that painting may hp re-InscrIbed with critical potential. This re-Inscr-iption is proposed as operating by way of the adoption of cer-taln formal and conceptual strategies, these being parody, metonymy and readvrnades. Whilst these strategies have wider relevance in contemporary debates many of which emanate from critiques of Neo-expressionism - they are of also of primary importance to a re-artlculatlon of painting within my own practice.
A Dissertation submitted to the Faculty of Arts. University of the Witwatersrand. Johannesburg, in partial fulfillment of the requirements for degree of Master 0f Arts in Fine Arts. Johannesburg 1996,